Fetofetal transfusion syndrome: do the neonatal criteria apply in utero?. Issue 7 (July 1990) - Fisk, N M; Borrell, A; Hubinont, C; Tannirandorn, Y; Nicolini, U; Rodeck, C H
Abstract : Thirteen fetuses (five twin, one triplet) were compromised by fetofetal transfusion syndrome in six pregnancies, five in the mid trimester, and one in the third trimester. This diagnosis, which was suspected because of ultrasound findings of discordant growth, discordant amniotic fluid volumes, concordant external genitalia, and monochorial placentation, was confirmed postnatally in each. Nine fetuses underwent blood sampling to aid diagnosis and assessment of fetal wellbeing. In contrast to fetofetal transfusion syndrome investigated postnatally, a difference in haemoglobin concentration of 50 g/l or more in utero was found in only one pregnancy, which was near term, although all had fetal erythroblastaemia and a difference in weight of 20% or more. In vivo confirmation of shared circulation was achieved in two pregnancies by transfusing adult Rh negative red cells into the smaller fetus and then detecting them by Kleihauer testing in blood aspirated from the larger. Invasive procedures also yielded information on fetal blood gas measurements (acidaemia in four and hypoxaemia in six) and amniotic pressure (raised in two). We suggest that comparison of haemoglobin concentrations is inaccurate in fetofetal transfusion syndrome in utero, the diagnosis of which may necessitate detection of a shared circulation using a marker such as adult red cells.